Privileged locations and role of native informants in Khaled Hoessini’s The Kite Runner: A self-orientalist study - Akhter, Shamim; Riaz, Wajid; Ambasta, Anurag; Kumar, Madhur; Kumar, Tribhuwan (Research Journal in Advanced Humanities, 2025)
The purpose of the study is to analyze Khalid Hoessini’s The Kite Runner (2005) from a Self-Orientalized perspective to show the privileged location and role of native informants, and the stereotypical images of the Oriental are given in The Kite Runner by the writer as a native informant. The mythological approach is qualitative and the nature of the research is analytical, and the researcher used close textual as a research method. Daura (1995) and Spivak’s (1999) notions of self-Orientalism and native informants have been respectively used as theoretical framework. Hosseini (2005) is a true Self-Orientalist in Daura’s (1995) point of view with reference to Said’ s Orientalism (1978), and also a factual follower as a native informant who gave stereotypical images of Afghan in The Kite Runner (2005), and misrepresented the Oriental as Orientalists misrepresented, showing the orient as Others. The main findings of the research are effective for the researchers and scholars of literature who after comprehension the concept of native informants who re-Orientalize the Orient may research and approach the notions in other discourses of developing countries. Orientalists have represented the Orient in their writings, and the approach is identified as Orientalism.